Exploration of carboxymethyl guargum grafted hyperbranched poly(acrylic acid) as a scaffold for silver nanoparticles for ultrafast and selective sensing of Hg(ii). (1st November 2017) - Das, Tamalika; Sengupta, Srijoni; Dey, Ayan; Pal, Abhijit; Saha, Suparna; Bandyopadhyay, Abhijit
Abstract : A sensor for Hg 2+ was developed from a system of silver nanoparticles stabilized by polysaccharide grafted hyperbranched poly(acrylic acid). Abstract : Carboxymethyl guargum- g -poly(acrylic acid)- co -poly(divinyl benzene), bCMGG- g -HBPAA, having an unprecedented hyperbranched architecture is developed. A combination of a polymer grafting technique and "Strathclyde methodology" in emulsion is followed for the first time in the synthesis of bCMGG- g -HBPAA. FTIR, NMR, intrinsic viscosity and linear viscoelasticity studies confirm the microstructure of bCMGG- g -HBPAA. Owing to the unique properties of polysaccharide and hyperbranched chains, bCMGG- g -HBPAA successfully stabilizes monodispersed silver nanoparticles (AgNPs-HB) of size 27 nm and with good optical clarity. AgNPs-HB forms an amalgam in the presence of Hg 2+ and thus facilitates colorimetric detection/accurate estimation of Hg 2+ (up to 1 ppb). Furthermore, for the first time it is shown that the specificity and sensitivity of AgNPs-HB based sensors towards Hg 2+ sensing can be enhanced in the presence of Na salt catalysts. The working principle of AgNPs-HB and AgNPs-HB/Na salt(s) based sensors for Hg 2+ is explained through UV-Vis, XRD, HRTEM and CV studies.